2022
DOI: 10.1097/md.0000000000030547
|View full text |Cite
|
Sign up to set email alerts
|

Stress levels of nursing students: A systematic review and meta-analysis

Abstract: Context: Nursing students experience psychosocial stress in their workplace. Available statistics are at variance, and hence, the need to know the overall prevalence of psychosocial stress among nursing students.Aims: This study aimed to determine the prevalence of psychosocial stress among nursing students through meta-analysis.Materials and methods: PubMed, Cochrane, Web of Science, CNKI, and China Biomedical Literature Service System were searched for articles. Search terms include "psychosocial stress," "n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 23 publications
0
13
1
Order By: Relevance
“…Studies in Vietnam [29] and Calabar, South-South Nigeria [21], reported high levels of stress among majority of the students studied, while a study in South-West Nigeria reported a low level of stress [20]. A meta-analysis involving 2 countries in Europe, 2 in Asia, and Saudi Arabia, also reported stress levels of intern nurses to be moderate [30], while a systematic review in Middle East and North Africa reported the prevalence range of low perceived stress of 0.8-65%, moderate stress of 5.9-84.5%, and high stress of 6.7-99.2% [31]. It is crucial to note that low or moderate levels of stress may enhance students' motivation, leading to greater perseverance when studying and achieving future goals.…”
Section: Correlation Of Stress Indices and Socio-demographic Characte...mentioning
confidence: 99%
“…Studies in Vietnam [29] and Calabar, South-South Nigeria [21], reported high levels of stress among majority of the students studied, while a study in South-West Nigeria reported a low level of stress [20]. A meta-analysis involving 2 countries in Europe, 2 in Asia, and Saudi Arabia, also reported stress levels of intern nurses to be moderate [30], while a systematic review in Middle East and North Africa reported the prevalence range of low perceived stress of 0.8-65%, moderate stress of 5.9-84.5%, and high stress of 6.7-99.2% [31]. It is crucial to note that low or moderate levels of stress may enhance students' motivation, leading to greater perseverance when studying and achieving future goals.…”
Section: Correlation Of Stress Indices and Socio-demographic Characte...mentioning
confidence: 99%
“…Over the past three decades, stress and coping in student nurses have been extensively researched, resulting in a substantial volume of individual studies and literature reviews [11,12]. Guided by the Joanna Briggs Institute (JBI) methodology, this umbrella review aims to examine the current state of knowledge on stress and coping in student nurses during their prelicensure programs [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…Nursing has been a female-dominated profession for decades and research shows that female gender predicts and is associated with depressive symptoms with significantly different effects than males in college students ( Facioli et al, 2020 , Mofatteh, 2021 , Yu et al, 2021 ). Among the various fields of medical sciences, nursing students have been found to face more stressors during their study period and are more at risk of suffering depressive symptoms than other students ( Ching et al, 2020 , Lee, 2019 , Zheng et al, 2022 ). This stress and health impact could result from gender imbalance in the ratio of males and females among nursing students.…”
Section: Introductionmentioning
confidence: 99%